2020
DOI: 10.1038/s41419-020-02978-w
|View full text |Cite
|
Sign up to set email alerts
|

CCL18-induced LINC00319 promotes proliferation and metastasis in oral squamous cell carcinoma via the miR-199a-5p/FZD4 axis

Abstract: Long non-coding RNAs (lncRNAs), which may be modulated by chemokines, are key regulators in many cancers including oral squamous cell carcinoma (OSCC). An understanding of lncRNAs involved in chemokine (CC motif) ligand 18 (CCL18)-induced OSCC promotion remains elusive. The present study using lncRNA sequencing found LINC00319 to be significantly upregulated in OSCC cells subjected to rCCL18 stimulation. Furthermore, LINC00319 knockdown was found to attenuate the carcinogenic function of CCL18 in OSCC, reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Accumulating evidence suggests that lncRNAs may act as ceRNAs for particular miRNAs to modulate the target genes of the miRNAs, including GC [ 43 , 44 ]. In this study, we assessed the subcellular localization of LINC01207 and observed that majority of LINC01207 were located in the cytoplasm of OSCC cells, which suggested that LINC01207 may function as a ceRNA for sponging miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that lncRNAs may act as ceRNAs for particular miRNAs to modulate the target genes of the miRNAs, including GC [ 43 , 44 ]. In this study, we assessed the subcellular localization of LINC01207 and observed that majority of LINC01207 were located in the cytoplasm of OSCC cells, which suggested that LINC01207 may function as a ceRNA for sponging miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 22 ] reported for the first time that CCL18 was up-regulated in bladder cancer (BC) cells, which further promote cell migration, invasion and epithelial-mesenchymal transition (EMT). CCL18 overexpression has also been revealed to be associated with the proliferation, invasiveness, and angiogenesis of oral cancer cells, as well as the TNM stage [ 30 ]. However, there was no study investigating the role in PCPG.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when the lncRNA LEF1-AS1 was silenced, it caused the arrest of the G0/G1 cell cycle and suppressed cell proliferation and growth in vitro via inactivation of the Hippo signaling pathway [ 59 ]. Furthermore, some certain lncRNAs were verified to promote OSCC invasion, metastasis, and angiogenesis [ 62 , 103 ]. For example, MALAT-1 is closely related to the growth and metastasis of OSCC cells and through the regulation of target small proline-rich protein (SPRR) in order to promote distant metastasis [ 77 ].…”
Section: Roles Of Lncrna In Osccmentioning
confidence: 99%
“…For example, MALAT-1 is closely related to the growth and metastasis of OSCC cells and through the regulation of target small proline-rich protein (SPRR) in order to promote distant metastasis [ 77 ]. LINC00319 is downstream of Chemokine ligand 18 (CCL18), and overexpression of LINC00319 regulated the expression of VEGFA and MMP-9 to promote the angiogenic ability of OSCC cells [ 62 ]. Similarly, knockdown of FOXCUT led to the downregulation of angiogenesis factor VEGFA in Tca8113 and SCC9 cells, which indicated the potential function for FOXCUT in angiogenesis of OSCC [ 43 ].…”
Section: Roles Of Lncrna In Osccmentioning
confidence: 99%